Cosubstrate strategy for enhancing lignocellulose degradation during rumen fermentation in vitro: Characteristics and microorganism composition. (July 2020) - Xing, Bao-Shan; Han, Yule; Cao, Sifan; Wen, Junwei; Zhang, Kaidi; Yuan, Honglin; Wang, Xiaochang C.
Abstract: To enhance the degradation of wheat straw (WS) and corn straw (CS) in rumen fermentation, characterization of degradation and ruminal microorganisms of monosubstrate (WS/CS) groups and a cosubstrate strategy with food waste (FW) group was performed. The cellulose, hemicellulose, and lignin degradation efficiency of WS and CS; soluble chemical oxygen demand; volatile fatty acid yields; and activity of ligninolytic, cellulolytic, and hemicellulolytic enzymes for the cosubstrate group were improved compared with those for the corresponding monosubstrate groups. An accurate and a good of fit of the Weibull kinetic model, decreased crystallinity index values, and characteristic absorbance bands in the Fourier transform-infrared spectra further confirmed that cosubstrate addition with FW decreased the resistance of cellulose and hemicellulose to biodegradation. High-throughput sequencing results suggested that the bacterial diversity in CS rumen fermentation and fungal diversity and richness in WS rumen fermentation were promoted with FW as a cosubstrate. The cosubstrate addition with FW significantly affected the composition of the ruminal bacteria and fungi in rumen fermentation. The relative abundances (RAs) of rumen bacteria were increased in the cosubstrate CS/WS and FW fermentation conditions, and the enhancement of CS degradation with FW supplementation was stronger than that of WS rumen fermentation with FW supplementation. The RAs of the ruminal fungal genera Ustilago and Fusarium were promoted in CS and WS fermentation with FW, respectively. Moreover, the fermentation properties and rumen flora in the FW rumen fermentation also provided some evidence to suggest an enhancement of the cosubstrate strategy compared with the monosubstrate strategy. Graphical abstract: Image 1 Highlights: Food waste (FW) increased alkalinity and improved VFAs yield in rumen fermentation. Wheat/corn straw (WS/CS) rumen degradation was enhanced by cosubstrate with FW. Lignocellulases and bacterial diversity in CS and FW fermentation were improved. Fungal diversity and richness in WS fermentation were promoted with FW addition.